2001
DOI: 10.1002/14651858.cd003183
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal herbs for hepatitis C virus infection

Abstract: BackgroundHepatitis C virus (HCV) infection is a serious health problem world-wide. Medicinal herbs are increasingly being used for hepatitis C. ObjectivesTo assess the efficacy and safety of medicinal herbs for hepatitis C virus infection. Search methodsSearches were applied to The Controlled Trial Registers of The Cochrane Hepato-Biliary Group, The Cochrane Complementary Medicine Field, and The Cochrane Library as well as MEDLINE, EMBASE, BIOSIS, Chinese and Japanese databases (February 2001). Five Chinese a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 46 publications
0
31
1
Order By: Relevance
“…27 Most studies of CAM therapy have been hampered by the small numbers of patients evaluated, the inclusion of patients with varying forms of hepatitis, and the lack of randomization or placebo controls. 19,28 Prospective, adequately powered, randomized, controlled trials of potentially effective herbal medications are needed.…”
Section: Management Of the Difficult-to-treat Patients With Hepatitis Cmentioning
confidence: 99%
“…27 Most studies of CAM therapy have been hampered by the small numbers of patients evaluated, the inclusion of patients with varying forms of hepatitis, and the lack of randomization or placebo controls. 19,28 Prospective, adequately powered, randomized, controlled trials of potentially effective herbal medications are needed.…”
Section: Management Of the Difficult-to-treat Patients With Hepatitis Cmentioning
confidence: 99%
“…Although the most preparations did not show positive effects on the clearance of serum HCV RNA or anti-HCV antibodies or on serum liver enzymes, silybin exhibited a significant effect, reducing serum aspartate aminotransferase and gamma-glutamyltranspeptidase activities [35,36]. The antiviral mechanism of silybin action is still unclear because its chemical and pharmacological properties may change when it is administered orally.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, 41% of patients reported use of these modalities, with 20% reporting use of herbal medicine, including sylamarin (12%), licorice root (glycyrrhizin) and St. John's wart [9] . In a review of medicinal herbs for HCV infection, the authors concluded that some of these agents may have an effect on liver enzymes but there is no firm evidence that supports their efficacy on chronic HCV [10] . In a recently published phase-I, open label clinical trial, 50 patients with chronic HCV infection were treated orally with a combination of seven antioxidative oral preparations (glycyrrhizin, schisandra, silymarin, ascorbic acid, lipoic acid, L-glutathione, and alpha-tocopherol) on a daily basis for 20 wk, along with four different intravenous preparations (glycyrrhizin, ascorbic acid, L-glutathione, B-complex) twice weekly for the first 10 wk [11] .…”
Section: Introductionmentioning
confidence: 99%